2022
DOI: 10.1186/s12302-022-00626-y
|View full text |Cite
|
Sign up to set email alerts
|

The influences of the COVID-19 pandemic on sustainable consumption: an international study

Abstract: Background Sustainable production and consumption are two important issues, which mutually interact. Whereas individuals have little direct influence on the former, they can play a key role on the latter. This paper describes the subject matter of sustainable consumption and outlines its key features. It also describes some international initiatives in this field. Results By means of an international survey, the study explores the emphasis given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…Even after the epidemic, personal selling may resume the use of environmentally friendly packaging, but packaging waste in online shopping may continue. Although there have been some studies on consumer behavioral changes in the use of plastic packaging during the pandemic ( Liu et al, 2021 ; Leal Filho et al, 2022 ), there is still a lack of similar research on consumers’ willingness to accept circular packaging for online shopping. Therefore, the main purpose of this study was to explore which factors prompt consumers to accept and use circular packaging when they shopped online.…”
Section: Introductionmentioning
confidence: 99%
“…Even after the epidemic, personal selling may resume the use of environmentally friendly packaging, but packaging waste in online shopping may continue. Although there have been some studies on consumer behavioral changes in the use of plastic packaging during the pandemic ( Liu et al, 2021 ; Leal Filho et al, 2022 ), there is still a lack of similar research on consumers’ willingness to accept circular packaging for online shopping. Therefore, the main purpose of this study was to explore which factors prompt consumers to accept and use circular packaging when they shopped online.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Daryanto et al (2022) found, among Chinese adults, that individuals' beliefs that the pandemic had been caused by humanity's excessive intrusion into nature had a positive impact on their EA and this triggered a positive behavioural change towards the environment. Another study discovered that the pandemic was associated with an increase in pro-environmental consumption, particularly one's willingness to purchase green and sustainably manufactured products ( Leal Filho et al, 2022 ).…”
Section: Pro-environmental Behaviour's Correlates and Associated Hypo...mentioning
confidence: 99%
“…Furthermore, one of recent studies showed that the Covid-19 pandemic was also associated with an increase in PEB, whereby people attributed the cause of the pandemic to environmental factors such as climate change ( Daryanto et al, 2022 ). Another study discovered that the pandemic was associated with an increase in pro-environmental consumption, particularly one's willingness to purchase green and sustainably manufactured products ( Leal Filho et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has prompted a transition towards more sustainable consumption practices, as supported by scholarly research (Perkins et al, 2021). Different studies have shown an increase in PEB because of COVID: Italy (Dangelico et al, 2022), Spain (Li et al, 2021), the USA (Rodgers et al, 2021) and internationally (Leal Filho et al, 2022). According to Dangelico et al (2022), various changes regarding sustainable consumption have occurred during the pandemic.…”
Section: Pro-environmental Behavior and Covid-19mentioning
confidence: 99%